PENERAPAN ANALISIS REGRESI DUMMY PADA DATA KUALITATIF KASUS EKONOMI - Roza Zelvia (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2017)
Regression analysis is basically the study of the dependence of one variable dependent (response / non-free) with one or more variables independent (explanatory / free), in order to estimate and / or predict the average population or the average value of the variable dependent based on the value independent variables that are known. In some economy cases, we ussualy would like to look at the relationship between variabel, such as the relationship between the profit of the company with the types of company, income customers who finance with the amount of funding requested and the salary earned by the employees with education and work experience of the employee itself. However, dealing with the variables of economy cases, there are many variables that are ordinal or nominal scale called qualitative data. Therefore, it can not only be solved by using a simple regression analysis or multiple regressions. Moreover, Dummy regression analysis is one of the solutions in dealing with cases of economic data with qualitative independent variables. This paper will investigate the economic case data which have the categorical independent variables by using dummy regression analysis. The data used in this literature study is secondary data obtained from the data already published to the Internet. Furthermore, based on data analysis, it was found that, in the dummy regression analysis, it was allowed more than one Independent variables, where the variables can interact or have no interaction each other. Those can be drawn by a scatterplot of the data.